Impact of primary care on hospital admission rates for diabetes patients: a systematic review - Wolters, René; Braspenning, Johanna Catharina Cornelia; Wensing, Michel (Diabetes research and clinical practice, 2017)
High-quality primary care for diabetes patients may be related to lowered hospital admissions. A systematic search was performed to assess the impact of structure, process, and outcome of primary diabetes care on hospital admission rates, considering patient characteristics. Studies on diabetes patients in primary care with hospitalisation rates as outcomes published between January 1996 and December 2015 were included. Indicators of quality of care (access, continuity and structure of care, process, and outcome indicators) and patient characteristics (age, gender, ethnicity, insurance, socio-economic status, diabetes characteristics, co-morbidity, and health-related lifestyle) were extracted. After assessment of the strength of evidence, characteristics of care and diabetes patients were presented in relation to the likelihood of hospitalisation. Thirty-one studies were identified. A regular source of primary care and a well-controlled HbA1c level decreased the likelihood of hospitalisation. Other aspects of care were less consistent. Patients’ age, co-morbidity, and socio-economic status were related to higher hospitalisation. Gender and health-related lifestyle showed no relationship. Studies were heterogeneous in design, sample, and healthcare system. Different definitions of diabetes and unscheduled admissions limited comparisons. In healthcare systems where diabetes patients have a regular source of primary care, hospital admission rates cannot be meaningfully related to primary care characteristics.
Gesehen am 08.10.2018